2021
DOI: 10.3390/en14020312
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renewable Energy, Economic and Population Growth on CO2 Emissions in the East African Region: Evidence from Common Correlated Effect Means Group and Asymmetric Analysis

Abstract: This study aims to examine the asymmetric nexus between CO2 emissions and renewable energy and economic and population growth in seven East African countries (EACs) at the regional level and country levels. Common correlated effect means group (CCEMG), nonlinear autoregressive distributed lagged (NARDL), and causality tests were employed for the panel data from 1980 to 2016. The main findings are as follows: (1) Renewable energy consumption negatively affects CO2 emissions, while economic and population growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Their study found that there is a two-way symmetric relationship between economic growth and carbon dioxide emissions. Namahoro et al ( 2021 ) used panel data from 1980 to 2016, using nonlinear autoregressive distribution lag (NARDL) and causality tests, to study the population growth of seven East African countries (EACs) at the regional and national levels and the relationship between economic growth, carbon dioxide, and energy consumption. Their research found that there is an asymmetric relationship between economic growth and CO 2 emissions in different countries.…”
Section: Co 2 Emissions and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study found that there is a two-way symmetric relationship between economic growth and carbon dioxide emissions. Namahoro et al ( 2021 ) used panel data from 1980 to 2016, using nonlinear autoregressive distribution lag (NARDL) and causality tests, to study the population growth of seven East African countries (EACs) at the regional and national levels and the relationship between economic growth, carbon dioxide, and energy consumption. Their research found that there is an asymmetric relationship between economic growth and CO 2 emissions in different countries.…”
Section: Co 2 Emissions and Economic Growthmentioning
confidence: 99%
“…From our literature review, some scholars have recently studied the ARDL model (Adamu et al, 2020 ; Kong, 2021 ; Mongo et al, 2021 ; Yang et al, 2021a , b ), and some scholars use the NARDL model (Ghazouani, 2021 ; Namahoro et al, 2021 ), and Xiangyu et al ( 2021 ) use the QARDL model for empirical testing. The Fourier ARDL model, we used, is similar to the newly developed ARDL, but it uses bootstrap Monte Carlo simulation to make the results of the variable test more delicated.…”
Section: Co 2 Emissions and Economic Growthmentioning
confidence: 99%
“…Using the ARDL, Ali et al (2021) detected a positive relationship between economic growth and CO 2 emissions in Pakistan covering 1971-2014. Namahoro et al (2021) investigated the asymmetric association between CO 2 emissions and economic growth in seven East African countries. The empirical analysis uncovered that economic growth has a positive linkage with CO 2 emissions at the regional level; however, across the country level, the association was volatile.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, industrial transfer may indirectly affect CO 2 emissions by acting on economic development. With the development of China’s economy and the improvement of people’s living standards, residents’ household consumption has become an important source of energy consumption [ 46 ], and the increase in population has proven to be one of the main factors that promote CO 2 emissions [ 47 , 48 ].To some extent, industrial transfer means labour force transfer because upgrading the regional industrial structure may become the pull force of population migration [ 34 ]. Therefore, industrial transfer may have a significant impact on CO 2 emissions through its impact on the population.…”
Section: Industrial Transfer and Co 2 Emissions: Literature Review And Analysis Frameworkmentioning
confidence: 99%